2012
DOI: 10.1002/hep.25912
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of microRNA-122 causes hepatic insulin resistance by inducing protein tyrosine phosphatase 1B, which is reversed by licorice flavonoid

Abstract: Protein tyrosine phosphatase 1B (PTP1B) inhibits hepatic insulin signaling by dephosphorylating tyrosine residues in insulin receptor (IR) and insulin receptor substrate (IRS). MicroRNAs may modulate metabolic functions. In view of the lack of understanding of the regulatory mechanism of PTP1B and its chemical inhibitors, this study investigated whether dysregulation of specific microRNA causes PTP1B-mediated hepatic insulin resistance, and if so, what the underlying basis is. In high-fat-diet-fed mice or hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 41 publications
(57 reference statements)
5
91
0
2
Order By: Relevance
“…Interestingly, some chemical compounds, e.g. licorice flavonoids and linoleic acid, regulated miRNAs and attenuated the pathogenesis of diabetes (Parra et al 2010, Yang et al 2012. The development of chemical compounds to regulate miRNAs implicated in diabetes could be another potential strategy to manipulate diabetes.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, some chemical compounds, e.g. licorice flavonoids and linoleic acid, regulated miRNAs and attenuated the pathogenesis of diabetes (Parra et al 2010, Yang et al 2012. The development of chemical compounds to regulate miRNAs implicated in diabetes could be another potential strategy to manipulate diabetes.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…Protein tyrosine phosphatase 1B (PTP1B), a target of miR-122, inhibits hepatic insulin signaling by dephosphorylating tyrosine residues in the insulin receptor (IR) and IRS. A high-fat diet induces the phosphorylation of JUNK1 in mice, and decreases the expression of miR-122, resulting in an increase in hepatic insulin resistance (Yang et al 2012). Another study has shown that the reduction in miR-200a/b/c in the livers of db/db mice is associated with the inactivation of the AKT/GSK signaling pathway.…”
Section: Mirnas and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Protein tyrosine phosphatase 1B (PTP1B), a target of miR-122, inhibits hepatic insulin signaling by dephosphorylating insulin receptor and IRS. In high-fat-diet-fed mice and hepatocyte models with insulin resistance, the expression of miR-122 is downregulated [71].…”
Section: Mirna Regulation Of Insulin Secretion and Signalingmentioning
confidence: 99%
“…Currently there has been a lot of focus on the microRNA (miR)-122 to understand the genetics of hepatocellular carcinoma (HCC), pathology of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, hepatic insulin resistance, and lipid metabolism (1)(2)(3)(4). Interestingly, miR-122 expression levels were significantly reduced than the normal levels in HBV-associated liver cancer, but not in HCV related liver cancer (5).…”
mentioning
confidence: 99%